2010
DOI: 10.1007/s10659-010-9287-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plane-Strain Crack Problems (Mode-I & Mode-II) in the Presence of Surface Elasticity

Abstract: We consider plane deformations of a linearly elastic solid in the case where either a mode-I or mode-II crack is present but, perhaps more significantly, when surface effects are included in the mechanics of the crack faces. The surface effects lead to a more accurate description of deformation and are incorporated using a version of the continuum based surface/interface model of Gurtin and Murdoch. We obtain a semi-analytic solution valid throughout the entire domain of interest (including at the crack tips) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 33 publications
1
58
1
Order By: Relevance
“…By using the Green's function method, the original boundary value problem is finally reduced to a system of Cauchy singular integro-differential equations. When the bulk materials are isotropic, our obtained singular integro-differential equations reduce to those by Kim et al (2010Kim et al ( , 2011a. Thus the correctness of the proposed Green's function method is verified.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…By using the Green's function method, the original boundary value problem is finally reduced to a system of Cauchy singular integro-differential equations. When the bulk materials are isotropic, our obtained singular integro-differential equations reduce to those by Kim et al (2010Kim et al ( , 2011a. Thus the correctness of the proposed Green's function method is verified.…”
Section: Introductionmentioning
confidence: 59%
“…If a homogeneous plane is elastically isotropic with shear modulus µ and Poisson's ratio ν and the crack surface is also isotropic with surface Lame constants s λ and s µ , we have (Ting, 1996;Kim et al, 2010Kim et al, , 2011a:…”
Section: A Crack In a Homogeneous Isotropic Planementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there have been several papers (see Kim, Schiavone and Ru [21,23,24], Kim, Ru and Schiavone [22], Antipov and Schiavone [1]) that study fracture in brittle materials appealing to an approach by Murdoch and Gurtin [19] that introduces surface elasticity at the surface of cracks. These studies modify the classical linearized elasticity theory by allowing for elastic surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Ru's solution indicates that, when the asymptotic behavior of the harmonic materials satisfies the constitutive restriction proposed by Knowles and Sternberg [1975], the oscillatory singularity again disappears. Most recently, various authors (see, for example, [Kim et al 2010b;2011a;2011b;2011c;Antipov and Schiavone 2011;Wang 2015]) have incorporated the continuum-based surface/interface theory of Gurtin and Murdoch [1975;1978;Gurtin et al 1998] into the fracture analysis of linearly elastic solids. It was shown that the incorporation of the Gurtin-Murdoch surface model can suppress the classical strong square-root stress/strain singularity at the crack tip predicted in linear elastic fracture mechanics (LEFM) to the weaker logarithmic singularity [Walton 2012;Kim et al 2013].…”
Section: Introductionmentioning
confidence: 99%